Analysing Deep Meaning of Proverbs in Pashto Language - Safa, Mohammad Mustafa; Hemat, Mohammad Amin (RIRAI Publisher, 2025)
As other ancient languages of the world, Pashto is one of them having rich folkloric literature. One of the most important part of this literature is proverbs, which makes a special part of history of this language. These proverbs shows different life styles , culture, customs , historical events and lifel lessons. In Pashto proverbs are easy and simple in form but deep in meaning. Some proverbs in Pashto language are having a story or social event behind them. If we do not know about these events and stories it mean we cant understand their meaning and usage. Therefore the first meaning of these proverbs is real and the second meaning acts as irony. For example: (A broken hand lies in the neck.) Its meaning is clear that we cant move a broken hand we tie it in our neck so it can heal, but its ironical meaning is that when there is a criminal or poor person in our society, all members of the society are responsible for their actions, they should endure them until finding a way of solution. In the last thousands of years researchers have collected thousands of proverbs in Pashto language, that is why we have used library method in our research . There are still works to be done in researching and collecting proverbs in Pashto language. It is very important to translate this cultural heritage to other languages so their speakers can understand its meaning.